Clinical course of duodenal mucosa‐associated lymphoid tissue lymphoma: Comparison with gastric mucosa‐associated lymphoid tissue lymphoma. Issue 2 (21st July 2020) - Na, Hee Kyong; Won, Sung Hyun; Ahn, Ji Yong; Kim, Ga Hee; Jung, Kee Wook; Lee, Jeong Hoon; Kim, Do Hoon; Choi, Kee Don; Song, Ho June; Lee, Gin Hyug; Jung, Hwoon‐Yong; Kim, Hwa Jung
Abstract: Background and Aim: There are few cases of duodenal mucosa‐associated lymphoid tissue (MALT) lymphoma reported in the literature, and little is known about the clinical course of this disease. Here, we aimed to characterize the clinical features of duodenal MALT lymphoma by comparison with gastric MALT lymphoma. Methods: Thirteen patients diagnosed with duodenal MALT lymphoma at Asan Medical Center from March 1997 to February 2017 were included in this retrospective study, along with patients with gastric MALT lymphoma, matched by age and sex at a 1:10 ratio. Results: Median age of patients with duodenal MALT lymphoma was 49 (range 20–72) years, and 53.8% (7/13) were male. Comparison of patient characteristics indicated that Helicobacter pylori infection (46.2% vs 90.8%, P  < 0.001) and lymph node metastasis (23.1% vs 5.4%, P  = 0.049) rates differed between patients with duodenal and gastric MALT lymphoma. Overall complete remission (61.5% vs 86.2%, P  = 0.021) and complete remission after initial H. pylori eradication therapy (50% vs 87.7%, P  = 0.037) were significantly lower in patients with duodenal than gastric MALT lymphoma. Complications including bleeding, stricture, and transformation to high‐grade lymphoma occurred in a total of seven patients (4.9%), with a higher incidence in patients with duodenal than gastric MALT lymphoma (38.5% vs 1.5%, P  < 0.001). Conclusions: Duodenal MALT lymphoma is very rare, and treatment outcomes appear to be inferior to those of gastric MALT lymphoma.